Faculty of Business and Management, UiTM Puncak Alam – International Financial Literacy Program in Jakarta, Indonesia (13 – 20 May 2023) - UiTM, Faculty of Business and Management (UiTM, 2023)
The Faculty of Business and Management, UiTM Puncak Alam, successfully conducted the International Financial Literacy Program in Jakarta, Indonesia, from 13 to 20 May 2023. The program aimed to enhance financial knowledge and awareness among participants through knowledge sharing, interactive sessions, and cross-cultural engagement, while strengthening international collaboration and promoting financial literacy at a global level.